Existing in harmony : the postmodernism-religion reconciliation - Zaidah Rahmat (2009)
Lyotard defines the postmodern as “incredulity towards metanarratives.” Indeed, the rise of existential and postmodern ideas has meant the relinquishing of religious ideals in society and in Literature. However, even with postmodernism’s strong sense of disapproval of religious doctrines, it is peculiar to see that religion is still very much employed in postmodern literature. It also looks like this compulsion to include religion in such literature has the effect of legitimising readings of the text from a religious lens. Because of this, works of postmodern literature can also be interpreted as portraying religion positively instead of the commonly thought “purging” effect they have on religious ideals. By “positive portrayal” I mean that postmodern texts do not show religion to be an oppressive, antagonistic “concept”. My thesis explores postmodern literature “mogul” Samuel Beckett’s work from a religious standpoint to show how his works have the potential to become advocators of religion. I will also push this argument further and examine works by British playwright Harold Pinter, Irish writer Flann O’Brien and American writer Thomas Pynchon to show that Beckett is not the only writer who writes favourably about religion, and that such a “trend” is pretty widespread. In a nutshell, my thesis is incredulous towards the incredulity towards metanarratives and will seek to show that works of postmodernism are not as anti-religion as previously thought. The primary texts that will be used in this thesis is Beckett’s Waiting for Godot, Pinter’s The Caretaker, O’Brien’s The Third Policeman and Pynchon’s The Crying of Lot 49.